2007
DOI: 10.1037/0278-6133.26.2.174
|View full text |Cite
|
Sign up to set email alerts
|

Effects of written emotional expression: The role of positive expectancies.

Abstract: Objective: Writing in an emotional way about stressful or traumatic experiences has beneficial effects on emotional well-being and physical health. Yet the mechanisms that underlie these effects still need to be explored. Integrating research on the effects of positive expectancies, the authors suggest that positive effects of written emotional expression may, in part, depend on expectancies induced by writing about emotional experiences. Design: Two studies were conducted to test this hypothesis. In both stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 54 publications
0
20
0
Order By: Relevance
“…Furthermore, communicating via online message boards involves written rather than oral communication. The process of actively writing about one's feelings and emotions has been shown to be benefi cial in terms of emotional well-being (Pennebaker and Beall, 1986;Pennebaker et al, 1990), reductions in self-reported symptoms (Broderick et al, 2005) and improvements in mood (Langens and Schüler, 2007). Exploring the interactions that take place on an online arthritis message board may provide insight into the social support sought and offered, as well as highlighting the group's needs that perhaps are not being brought up or addressed in the more formal and often time-pressured face-to-face interactions held in the clinical setting.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, communicating via online message boards involves written rather than oral communication. The process of actively writing about one's feelings and emotions has been shown to be benefi cial in terms of emotional well-being (Pennebaker and Beall, 1986;Pennebaker et al, 1990), reductions in self-reported symptoms (Broderick et al, 2005) and improvements in mood (Langens and Schüler, 2007). Exploring the interactions that take place on an online arthritis message board may provide insight into the social support sought and offered, as well as highlighting the group's needs that perhaps are not being brought up or addressed in the more formal and often time-pressured face-to-face interactions held in the clinical setting.…”
Section: Introductionmentioning
confidence: 99%
“…Written emotional expression provides an opportunity for individuals to confront traumatic experiences and it may create positive outcome expectancies for emotion regulation (77,78). In a small HAART era RCT, HIV-positive men and women were randomized to 4 sessions of writing about their worst stressful event or writing about trivial daily events (79).…”
Section: Written Emotional Expression Interventionsmentioning
confidence: 99%
“…To carry this further, an individual holds expectations about her self-regulation abilities (Langens, 2007;Scheier & Carver, 2003), and so the modulation of emotional responses rests upon a variety of selfefficacy beliefs that may be developed and enriched through writing expressively. If this is the case, then control perceptions are generally relevant to the connection between writing and health, as they dictate what one expects from writing and from one's pursuits in life (for an extended discussion, see Langens & Schü ler, 2007), regardless of what is realistic and/or practical. In order to appreciate how perceived control could fit into a model of writing and health, it is first useful to show how the theoretical problems of the writing paradigm are likely a result of its vast and thus self-fulfilling directions.…”
Section: Habituation (''Exposure'') Theorymentioning
confidence: 98%